FAKTOR-FAKTOR YANG MEMPENGARUHI PREFERENSI PETANI TERHADAP USAHATANI JAGUNG HIBDRIDA DI DESA LAIBA KECAMATAN PARIGI KABUPATEN MUNA - Andi Soleh; Hartina Batoa; Mardin Mardin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
This research was motivated by farmers' preference on hybrid corn farming in Laiba village, Parigi sub-district, Muna district. This research aims to find out the factors that influence farmers' preference on hybrid corn farming in Laiba Village, Muna Regency. Determination of respondents in this study used census technique by taking all hybrid corn farmers which amounted to ten farmers. The data collection process was conducted by observation, interview and documentation. Data analysis used qualitative descriptive analysis. Data analysis in this study used the research model conducted by Miles and Huberman (1984), namely qualitative data analysis which is carried out interactively and takes place continuously so that it is complete until saturation. Therefore, data analysis in this study includes (data reduction), (data presentation) and (conclusion drawing). The results showed that farmers' preferences are used to determine farmer satisfaction decisions with limited choices and resources so that the utility value obtained reaches the optimum.